Women’s health in prison situations in Brazil - Oliveira, Ewerton Santos; Amaral , Anne Caroline Santana; de Oliveira , Jucilene Nascimento; Rodrigues, Wellington Pereira (Seven Editora, 2023)
Health System (SUS) obtains from some policies that aim to ensure the best health condition for the population. In this perspective, when analyzing women in penitentiary situations, they tend to suffer from more injuries and in a certain way a vulnerability in their health due to the proportions to which they are submitted. DOI: https://doi.org/10.56238/thebestiimulti2022-003